RANCANG BANGUN SIMULASI KONTROL LAMPU OPERASI DENGAN IR REMOTE DAN MANTION DETECTOR - M. Jidan Khoir; Fitria Priyulida (JURNAL MUTIARA ELEKTROMEDIK, 2019)
Operating lamp is a surgical instrument used for lighting during surgery in the operating room. The main function is to illuminate objects during surgery which are placed in the operating room and delivery room. This study aims to design an operating lamp control with an IR remote and a mention director to make it easier for users not to adjust the installation of operating lamps. all these systems are controlled by ATMega 328p. In this day and age more and more medical devices are very sophisticated so that it is easy and efficient in the use of and efficient in the use of electric current so that with the tone of this era the authors make a design and design simulation of operating lamp control with IR remote and mantion detector to save usage electric current and makes it easier for users to operate the operation lights by detecting motion sensors and remote IR so that the operating lights will only turn on when there are people on the operating table, so that the electric current used is far more efficient by using the Arduino Unu microcontroller, PIR sensor motion detector and IR Remote as the Remote controller Operating lights